From Shadow IT to Business-managed IT: a qualitative comparative analysis to determine configurations for successful management of IT by business entities - Andreas Kopper; Markus Westner; Susanne Strahringer (Information Systems and e-Business Management, 2020)
Shadow IT describes covert/hidden IT systems that are managed by business entities themselves. Additionally, there are also overt forms in practice, so-called Business-managed IT, which share most of the characteristics of Shadow IT. To better understand this phenomenon, we interviewed 29 executive IT managers about positive and negative cases of Shadow IT and Business-managed IT. By applying qualitative comparative analysis (QCA), we derived four conditions that characterize these cases: Aligned, local, simple, and volatile. The results show that there are three sufficient configurations of conditions that lead to a positive outcome; one of them even encompasses Shadow IT. The most important solution indicates that IT systems managed by business entities are viewed as being positive if they are aligned with the IT department and limited to local requirements. This allows to balance local responsiveness to changing requirements and global standardization. In contrast, IT systems that are not aligned and permanent (and either organization-wide or simple) are consistently considered as negative. Our study is the first empirical quantitative–qualitative study to shed light on the success and failure of Shadow IT and Business-managed IT.
Keywords: 650; Business-managed IT; Shadow IT; IT governance; Qualitative comparative analysis (QCA)